2000
DOI: 10.1097/00005382-200001000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Primary Bronchogenic Carcinoma After Heart or Lung Transplantation: Radiologic and Clinical Findings

Abstract: Chronic immunosuppression in organ transplant recipients predisposes to the development of malignant disease. The authors describe their 29-year institutional experience of bronchogenic carcinoma developing after heart and lung transplantation. Seven cases of bronchogenic carcinoma were diagnosed in 1,119 heart and lung transplant recipients. Computed tomography scans and radiographs at time of diagnosis, as well as prior radiographs available in six patients were retrospectively analyzed by two radiologists i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 23 publications
1
17
0
2
Order By: Relevance
“…Choi et al [24] identified pre-existing abnormalities by chest radiography around 12 months before eventual diagnosis in 66% of their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al [24] identified pre-existing abnormalities by chest radiography around 12 months before eventual diagnosis in 66% of their patients.…”
Section: Discussionmentioning
confidence: 99%
“…For kidney and heart transplant recipients, the prevalence of bronchogenic carcinoma has been found to range from 0.5% (kidney) to 2.8% (heart). [2][3][4] Now that lung transplantations throughout the world have been performed successfully for more than two decades, it has become possible to estimate the prevalence of lung cancer in lung transplant recipients.…”
Section: Introductionmentioning
confidence: 99%
“…We noted a wide variation in prevalence between more recent [7,12] and earlier reports [13,14]. The higher rates in the later studies were probably a consequence of the inclusion of older recipients, given the increasing age of patients undergoing transplantation, and the increase in the intensity of the immunosuppression regimen over time (a risk factor both by itself and as a contributor to patient longevity).…”
Section: Discussionmentioning
confidence: 60%
“…Years Location Cancer cases/total transplants Pathology Spiekerkoetter [13] 1987-1997 Germany 1/219 (0.46%) SCC Choi et al [14] 1968-1997 USA (CA) 1/99 (1.1%) SCC Arcasoy et al [12] 1991 efforts are recommended because aggressive management may be beneficial in patients with earlier stage disease.…”
Section: Authormentioning
confidence: 99%